The Youngsters and their Interior World during Corona Lockdown - Kaiter, Edith Hilde (Eximia, 2021)
The purpose of the present article is to present the everyday activities, thoughts and feelings of young people in the sad reality of the Corona lockdown. In the new world of the Corona pandemic, most youngsters, and not only, feel trapped, without perspectives, insecure, hopeless, worried, overwhelmed by fear, boredom and mistrust. The lockdown, the school closings and distance classes, the loneliness, the isolation, the fear and the uncertainty about the future have changed the whole life of the young people. In the imagination of the young people, trust is to be developed and openness, empathy, respect and appreciation to be shown to the other human beings are important prerequisites for future human relationships.